2013
DOI: 10.1097/ccm.0b013e3182668035
|View full text |Cite
|
Sign up to set email alerts
|

Electrographic Status Epilepticus Is Associated With Mortality and Worse Short-Term Outcome in Critically Ill Children*

Abstract: Objectives Electrographic seizures (ES) and electrographic status epilepticus (ESE) are common in critically ill children. We aimed to determine whether ES and ESE are associated with higher mortality or worse short-term neurologic outcome. Design Prospective observational study. Setting Pediatric intensive care unit of a tertiary children’s hospital. Patients Non-neonatal children admitted to a pediatric intensive care unit (PICU) with acute encephalopathy underwent continuous electroencephalographic (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
211
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 176 publications
(221 citation statements)
references
References 42 publications
9
211
1
Order By: Relevance
“…15,27 A number of single-center studies have demonstrated an association between electrographic seizures or electrographic status epilepticus and worse outcome in critically ill children. 11,12,14,16,17,28 Our data also indicate that electrographic status epilepticus was associated with higher mortality, even after adjusting for the neurologic diagnosis category and initial EEG background category. However, the current data cannot establish whether electrographic status epilepticus is a modifiable risk factor for mortality or is a nonmodifiable biomarker of severe brain injury leading to mortality.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…15,27 A number of single-center studies have demonstrated an association between electrographic seizures or electrographic status epilepticus and worse outcome in critically ill children. 11,12,14,16,17,28 Our data also indicate that electrographic status epilepticus was associated with higher mortality, even after adjusting for the neurologic diagnosis category and initial EEG background category. However, the current data cannot establish whether electrographic status epilepticus is a modifiable risk factor for mortality or is a nonmodifiable biomarker of severe brain injury leading to mortality.…”
supporting
confidence: 53%
“…Both this study and a prior single-center study reported worse short-term outcome with electrographic status epilepticus but not electrographic seizures. 16 If these data are replicated in studies with long-term outcome measures, then quantitative EEG methods may not need to identify every brief seizure if they can reliably identify a seizure burden that is sufficient to worsen outcome. There has also been interest in the use of more limited electrode montages in order to permit easier electrode application.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Encountering seizures is common for pediatrics residents working on inpatient wards, 1 and a rotation in pediatric neurology is a requirement of the Accreditation Council for Graduate Medical Education. 2 From our experience, teaching time-sensitive management of potentially lifethreatening conditions, including seizures, remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Ineffective management of seizures in adults can lead to status epilepticus (SE), and potentially worse patient outcomes. 1,3 At our institution, first-year residents (interns) are the primary providers and expected to execute timely management to avoid progression to SE.…”
Section: Introductionmentioning
confidence: 99%